AB0377 Clinical, Functional, and Structural Consequences of Targeting Low Disease Activity Rather than Remission in Early and Established Rheumatoid Arthritis Using Methotrexate or Methotrexate plus Adalimumab. (10th June 2014) - Aletaha, D.; Keystone, E.; Kupper, H.; Liu, S.; Florentinus, S.; van Vollenhoven, R.F.
Abstract : Background: Rheumatoid arthritis (RA) treat to target (tgt) recommendations advocate clinical remission (REM) as the tgt; targeting low disease activity (LDA) is an alternative for patients (pts) who cannot attain REM. Consequences of targeting LDA versus REM, or by using different definitions of REM, may vary based upon initial choice of therapy. Objectives: To evaluate week (wk) 52 consequences of achieving different tgts at wk26 in early and established RA pts treated with methotrexate (MTX) alone or adalimumab (ADA)+MTX. Methods: This post hoc analysis included pts treated with ADA+MTX or placebo (PBO)+MTX from 2 clinical trials in early RA (PREMIER 1, OPTIMA 2, 3 ) and 1 in established RA (DE019 4 ). Disease activity at wk26 was categorized as follows: LDA (2.6≤DAS28<3.2), and more stringent tgts of DAS28-REM (DAS28<2.6) and SDAI-REM (SDAI≤3.3). Clinical, functional, and radiographic outcomes at wk52 were assessed by DAS28, modified total Sharp score (mTSS), and disability index of the health assessment questionnaire (HAQ-DI), respectively. Results: In PREMIER, achieving wk26 REM (by DAS28 or SDAI) gave better clinical outcomes at wk52, while functional and structural results were comparable. ADA+MTX led to better clinical and structural outcomes compared to PBO+MTX, regardless of the tgt reached at wk26. In OPTIMA, where treatment was modified at wk26, no differences were seen between ADA+MTX and PBO+MTX, but there was a tendency for better clinical and radiological results if more stringent tgts were met at wk26. In DE019, stringent tgts led to better clinical and functional outcomes; ADA+MTX led to less structural progression compared to PBO+MTX, regardless of the tgt reached at wk26. Conclusions: In early RA, a more stringent wk26 tgt yields better clinical results at wk52. This is more apparent for radiographic outcomes with initial PBO+MTX than ADA+MTX, suggesting the choice of a stringent tgt is more relevant in pts treated with MTX alone. Treatment changes at wk26, in early RA, ensure proper radiographic inhibition and preservation of function. In established RA, stringent tgts should be pursued even though they are harder to achieve in practice. References: Breedveld FC et al. Arthritis Rheum 2006. Kavanaugh A et al. Ann Rheum Dis 2013. Smolen JS, et al. Lancet 2013. Keystone EC et al. Arthritis Rheum 2004. Acknowledgements: AbbVie sponsored the studies (NCT00195663 ; NCT00420927 ; NCT00195702 ), contributed to the design, and participated in collection, analysis, and interpretation of data, and in writing, reviewing, and approval of the final version. The authors would like to acknowledge Suchitrita Rathmann, of AbbVie, for her contribution to the statistical analyses. Medical writing support was provided by Jessica L. Suboticki, PhD, of AbbVie. Disclosure of Interest: D. Aletaha Grant/research support: AbbVie, Pfizer, Grünenthal, Merck, Medac, UCB, Mitsubishi/Tanabe, Janssen, and Roche, Consultant for: AbbVie, Pfizer, Grünenthal, Merck, Medac, UCB, Mitsubishi/Tanabe, Janssen, and Roche, E. Keystone Grant/research support: AbbVie, Amgen, AstraZeneca, BMS, Centocor, Genzyme, Merck, Novartis, Pfizer, Roche, and UCB, Consultant for: AbbVie, AstraZeneca, Biotest, BMS, Centocor, Genentech, Merck, Nycomed, Pfizer, Roche, and UCB, Speakers bureau: AbbVie, Amgen, BMS, Janssen, Merck, Pfizer, Roche, and UCB, H. Kupper Shareholder of: AbbVie, Employee of: AbbVie, S. Liu Shareholder of: AbbVie, Employee of: AbbVie, S. Florentinus Shareholder of: AbbVie, Employee of: AbbVie, R. van Vollenhoven Grant/research support: AbbVie Inc., BMS, Glaxo, HGS, MSD, Pfizer, Roche, and UCB, Consultant for: AbbVie Inc., BMS, Glaxo, HGS, MSD, Pfizer, Roche, and UCB DOI: 10.1136/annrheumdis-2014-eular.1129